1947
DOI: 10.1099/00221287-1-3-299
|View full text |Cite
|
Sign up to set email alerts
|

The Assimilation of Amino-acids by Bacteria: 4. The Action of Triphenylmethane Dyes on Glutamic Acid Assimilation

Abstract: SUMMARY:The level of glutamic acid concentration measured inside the streptococcal cell during assimilation represents a balance between the rate a t which the amino-acid is withdrawn from the external medium and the rate a t which it is metabolized within the cell.Treatment of the cells, prior to or during assimilation, with dyes of the triphenylmethane series results in raising the level of free glutamic acid attained within the cell. Evidence is presented that the triphenylmethane dyes prevent the metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1947
1947
1965
1965

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…The concentration of free amino-acids found inside the cell represents a balance between the rate at which they are utilized and the rate at which they are synthesized or taken up from the external medium (Gale & Mitchell, 1947). Consequently the appearance of free amino-acids inside a cell must mean that the amino-acids are either synthesized or taken from the medium at a rate greater than that at which they can be metabolized within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of free amino-acids found inside the cell represents a balance between the rate at which they are utilized and the rate at which they are synthesized or taken up from the external medium (Gale & Mitchell, 1947). Consequently the appearance of free amino-acids inside a cell must mean that the amino-acids are either synthesized or taken from the medium at a rate greater than that at which they can be metabolized within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…2 there is definitely an increase in turbidity a€ter the point a t which the internal concentration of glutamic acid begins to fall instead of to rise, and the internal concentration does not reach a new steady level until growth {as measured by turbidity increase) ceases. The glutamic acid which accumulates inside the cell acts as a reservoir of amino-acid for protein synthesis (Gale, 1947b) and for other metabolic purposes (Gale & Mitchell, 1947), and it may be that growth will continue as long as there is more than a certain limiting concentration within the cell. In that case the sequence of events would be: (i) penicillin prevents the passage of glutamic acid into the cell; (ii) the synthesis of protein, etc., proceeds a t the expense of the accumulated glutamic acid (and other aminoacids) within the cell and consequently the concentration falls; (iii) the internal concentration falls to the lowest level permitting synthesis of protein and growth ceases.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous paper (Gale & Mitchell, 1947) it was shown that some metabolism of glutamic acid took place after it had passed into the internal environment of the cell. This metabolism could be demonstrated since, if the amount of glutamic acid which accuniulated inside the cell during assimilation was compared with the amount which was removed from the external environment, there was on balance a ' disappearance ' of the amino-acid.…”
Section: Effect Of Penicillin O N Iiaterrzal It2etabolisin Of Glutainmentioning
confidence: 99%
See 2 more Smart Citations